THU0351 Vitamin D Insufficency Is Associated To Fatigue in Non-Supplemented Women with Systemic Lupus Erythematosus in A Mediterranean Region. (15th July 2016) - Salman-Monte, T.C.; Corzo, P.; Castro, F.; Polino, L.; Torrente-Segarra, V.; Carbonell-Abello, J.
Abstract : Objectives: It has been previously reported that vitamin D deficiency is more prevalent among SLE patients than in the general population. We sought to determine the prevalence of vitamin D insufficiency and deficiency and their related factors, its relationship to SLE symptoms and disease activity on a group of supplemented and non-supplemented female SLE patients from the Mediterranean region. Methods: We performed a cross-sectional study including female SLE patients who regularly attended the outpatient Lupus Unit at Parc de Salut Mar-IMAS in Barcelona, from January 2012 and May 2014. Collected data were: sociodemographics; vitamin D supplementation; fatigue degree visual analog scale; pharmacological treatment; main SLE serological markers, Indexes, scales; and plasma levels of 25-hydroxy vitamin D Results: One-hundred and two consecutive female SLE patients were included. Vitamin D overall insufficiency and deficiency were exhibited by 46% and 22.5% of patients, respectively. Vitamin D insufficiency was found in 50% of supplemented and 60% of non-supplemented patients. Among non-supplemented female SLE patients, it was found that patients with Vitamin D insufficiency showed more fatigue (p=0.009) and received more oral corticosteroids (p=0.02) than those with normal levels. Patients with Vitamin D insufficiency (supplemented and non-supplemented) received more oral corticosteroids than those without insufficiency (p=0.008). Conclusions: Vitamin D insufficiency is highly prevalent among female SLE patients, even in southern regions. Non-supplemented female SLE patients showed more fatigue and received more oral corticosteroids than those with normal levels of Vitamin D. This data was not found in supplemented patients despite having a high prevalence of Vitamin D insufficiency (up to 50%). Further studies with longer follow-up and larger population are needed to confirm our observations. Disclosure of Interest: None declared